Selected Decisions and Selected Documents of the International Monetary Fund. (Selected Decisions; Twenty-Fourth Issue, 1999, 1999)
The Thirty-Sixth Issue of Selected Decisions and Selected Documents of the International Monetary Fund includes decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF, as well as selected documents relevant to the current activities of the Fund.